Correlation of magnetic resonance imaging and post-ablation endoscopy to detect oesophageal thermal injury in patients after atrial fibrillation ablation: MRI-EDEL-study. Issue 7 (19th May 2020) - Halbfass, Philipp; Lehmkuhl, Lukas; Foldyna, Borek; Berkovitz, Artur; Sonne, Kai; Nentwich, Karin; Ene, Elena; Fochler, Franziska; Hörning, Frank; Matveeva, Anna; Lüsebrink, Ulrich; Deneke, Thomas
Abstract: Aims : To correlate oesophageal magnetic resonance imaging (MRI) abnormalities with ablation-induced oesophageal injury detected in endoscopy. Methods and results : Ablation-naïve patients with atrial fibrillation (AF), who underwent ablation using a contact force sensing irrigated radiofrequency ablation catheter, received a cardiac MRI on the day of ablation, and post-ablation oesophageal endoscopy (OE) 1 day after ablation. Two MRI expert readers recorded presence of abnormal oesophageal tissue signal intensities, defined as increased oesophageal signal in T2-fat-saturated (T2fs), short-tau inversion-recovery (STIR), or late gadolinium enhancement (LGE) sequences. Oesophageal endoscopy was performed by experienced operators. Finally, we correlated the presence of any affection with endoscopically detected oesophageal thermal lesions (EDEL). Among 50 consecutive patients (age 67 ± 7 years, 60% male), who received post-ablation MRI and OE, complete MRI data were available in 44 of 50 (88%) patients. In OE, 7 of 50 (14%) presented with EDEL (Category 1 lesion: erosion n = 3, Category 2 lesion: ulcer n = 4). Among those with EDEL, 6 of 7 (86%) patients presented with increased signal intensities in all three MRI sequences, while only 2 of 37 (5%) showed hyperintensities in all three MRI sequences and negative endoscopy. Correspondingly, sensitivity, specificity, positive predictive value, and negative predictive value (NPV) for MRI (increased signal in T2fs, STIR, and LGE) were 86%, 95%, 75%, and 97%, respectively. Conclusion : Increased signal intensity in T2fs, STIR, and LGE represents independent markers of EDEL. In particular, the combination of all three has the highest diagnostic value. Hence, MRI may represent an accurate, non-invasive method to exclude acute oesophageal injury after AF ablation (NPV: 97%).